Anticipation as a conscious acceleration of response time under conditions of initiative and counteraction with the enemy - Malkov, O. B.; Dementiev, V. L. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to consider the effect of anticipation on the performance of certain mental functions aimed at: reducing the response time to the enemy's influences; to reduce the time for the use of combat actions (methods) due to earlier determination of the moment of the start of an attack and automation of responses to a trigger signal.